Identification of Quaternary Sediments and the Existence of Biogenic Gas Sources in the Topang Delta, Meranti, Riau - Purnomo Raharjo; Mario Dwi Saputra; Delyuzar Illahude; Priatin Hadi Wijaya (Marine Geological Institute of Indonesia, 2019)
Delta Topang, located in Topang Island, Riau Province is known to have the potential of biogenic gas. This research was conducted to identify the Quaternary sediment and the existence of biogenic gas reservoar. In this research has been conducted 75 points of surface geoelectrical measurements (38 points in Parit Jawa and 37 points in Parit Bintang) and 2 points of core drilling (BH-1 in Parit Jawa and BH-2 in Parit Bintang). Total Organic Carbon was also carried out on 10 samples (5 samples from each drilling core). Based on resistivity value of geoelectrical measurements from all points, in general are determined 2 sediment types, very fine sediment (silt and clay) and fine sand. We discussed in detail only point 11 representing Parit Jawa region and point 39 representing Parit Bintang Village. Both in point 11 and point 39, very fine sediment was identified from the surface down to 59 m and 58.5 m respectively, mostly dominated by hydrous clay. Below these, very fine sediment is identified as fine sand. Core drilling BH-1 and BH-2 (40 m length each) composed of thick layer of hydrous clay from the core surface down to bottom part, intercalated with thin layers of silt and fine sand. We considered fine sand found at depths between 24 to > 90 m (from all geoelectrical measurement points) as the closure of biogenic gas. At Parit Jawa biogenic gas closures are found at 2 locations, which are in south west and north east measurement area. At Parit Bintang biogenic gas closures are found at 3 location which are one in south and two in north measurement area. Total organic carbon analyzed from BH-1 indicate the highest percentage at 26-27 m depth with percentage 71.6%. From BH-2 the highest value is indicated at 33-34 m depth with percentage 78.0%. From all this information it is known that the formation of biogenic gas from the abundance of TOC is in the layers of hydrous clay and clay where is in an anaerobic sulfate-reduction environment.Keyword: Quartenary sediment, biogenic gas, surface geoelectrical measurement, core drilling, total organic carbonDelta Topang, yang terletak di Pulau Topang, Distrik Rangsang, Kabupaten Meranti, Provinsi Riau pada diketahui memiliki potensi keberadaan gas biogenik. Penelitian ini dilakukan untuk Identifikasi Sedimen Kuarter dan keberadaan sumber gas biogenik. Pada penelitian ini telah dilakukan 75 titik pengukuran geolistrik permukaan (38 titik di Parit Jawa dan 37 titik di Parit Bintang). Pemboran inti dilakukan di dua lokasi antara lain BH-1 di Parit Jawa dan BH-2 di Parit Bintang. Analisa total karbon organik juga dilakukan pada 10 sampel (5 sampel dari setiap inti pemboran). Berdasarkan nilai resisitivitas pengukuran geolistrik dari semua titik, secara umum ditentukan 2 jenis sedimen, adalah sedimen yang sangat halus (lanau dan lempung jenuh air) dan pasir halus. Dalam makalah ini dibahas secara rinci hanya titik 11 yang mewakili Desa Parit Jawa dan titik 39 yang mewakili Desa Parit Bintang. Baik di Point 11 dan Point 39, sedimen yang sangat halus diidentifikasi dari permukaan hingga kedalaman 59 m dan kedalaman 58,5 m, yang didominasi oleh lempung jenuh air, di bawah sedimen yang sangat halus ini diidentifikasi sebagai pasir halus. Hasil pemboran inti BH-1 dan BH-2 (masing-masing 40 m) terdiri dari lapisan tebal lempung jenuh air dari permukaan, ke bagian bawah merupakan lapisan lanau dan pasir halus. Dari pengukuran geolistrik diperoleh pasir halus yang ditemukan pada kedalaman antara 24 m hingga lebih dari 90 m adalah sumber gas biogenik. Di Parit Jawa, sumber gas biogenik ditemukan di 2 lokasi, yaitu di barat daya dan timur laut daerah pengukuran. Di Parit Bintang sumber gas biogenik ditemukan di 3 lokasi yaitu satu di selatan dan dua di daerah pengukuran utara. Total karbon organik yang dianalisis dari BH-1 menunjukkan persentase tertinggi pada kedalaman 26-27 m dengan persentase 71,6%. Dari BH-2 nilai tertinggi ditunjukkan pada kedalaman 33-34 m dengan persentase 78,0%. Dari semua informasi ini diketahui bahwa pembentukan gas biogenik dari kelimpahan TOC, berada di lapisan lempung dan lempung jenuh air di mana berada dalam lingkungan reduksi sulfat anaerob.Kata kunci: Sedimen Kuarter, gas biogenik, pengukuran geolistrik permukaan, pemboran inti, total organic carbon